(untitled) (The Review of Diabetic Studies, 2025)
Type 2 diabetes mellitus (DM) is the most prevalent form of diabetes, accounting for over 90% of all cases worldwide. The increasing global burden of DM is partly attributable to a substantial population of individuals with undiagnosed type 2 DM who remain asymptomatic or untreated. Strengthening diagnostic capacities is therefore essential to facilitate timely intervention and improve clinical outcomes. Community engagement plays a pivotal role in mitigating the DM burden, with initiatives such as POSBINDU, a component of Community-Based Health Efforts (Upaya Kesehatan Berbasis Masyarakat, UKBM), and serving as a critical platform. However, POSBINDU cadres have yet to be systematically engaged in providing support and monitoring for survivors of natural disasters, particularly those lacking access to digital health applications. Advancements in health technology, exemplified by tools like Dering DM, offer significant potential to enhance self-management and improve the quality of life for individuals with DM. To further strengthen community participation, optimizing the role of POSBINDU cadres is imperative, ensuring their active involvement in both routine care and crisis response